EFEKTIVITAS PELAYANAN POSYANDU LANSIA DALAM MENINGKATKAN KUALITAS HIDUP LANSIA DI WILAYAH RT06/RW08 PONDOK KELAPA - Hastuti, Wedia; Dulame, Irma Maria (Publika Citra Media, 2025)
This study aims to analyze the effectiveness of Posyandu Lansia services in improving the quality of life of the elderly in RT06/RW08 Pondok Kelapa. The quality of life of the elderly is measured through the dimensions of physical, psychological, social, and environmental health. The research method used is quantitative with a pre-experimental one-group pretest-posttest design. A total of 30 elderly who actively participate in Posyandu Lansia activities in the area became the research sample. Data were collected through the WHOQOL-BREF questionnaire before and after participating in the Posyandu service program for a certain period of time. Data analysis was conducted using paired t-test to compare quality of life scores before and after the intervention. The results showed a significant increase in the quality of life scores of the elderly after participating in the Elderly Posyandu service, especially in the dimensions of physical and social health. It can be concluded that the Elderly Posyandu service is effective in improving the quality of life of the elderly in RT06/RW08 Pondok Kelapa.